Population structure and threats to sustainable management of woody plant species in a semi-arid agro-ecosystem in Nigeria (2016)
This study was conducted to assess population structure and threat to the sustainable management of woody species in the various ago-ecosystems in Dutsin-Ma Local Government Area (LGA) Katsina State, Nigeria. Purposive and stratified random sampling techniques were used to collect data from 21 randomly demarcated 100m × 100m sample plots. All woody plant species found in the sample plots with stem diameter >2 cm at 20cm above ground, were recorded. Population structure was summarized by diameter classes. For the identification of threats, field and questionnaire surveys were used. A total of 50 questionnaires were distributed at ten questionnaires per ward in five out of the 11 wards in the LGA. The highest numbers (350) of small diameter trees (0.1-1.0cm) were recorded in the agrosilvopastoral system. This was followed by silvopastoral and agrisilviculture systems with 89 and 85, respectively. However, the highest number of large diameter woody tree species was recorded in the silvopastoral system followed by agrosilvopastoral and agrisilviculture systems. The regular reverse J-shaped and fairly regular reverse J-shaped size class distribution observed for agrosilvopastoral and silvopastoral respectively, suggest a recuperating population. Over exploitation, debarking, de-branching, root-digging, leaf harvesting, seed harvesting, poor regeneration, slow rate of growth, wind effect and bush burning were the major threats to sustainable management of woody plant species in the study area. The implications of our findings for sustainable management of woody plant species in the study area are discussed and recommendations made.